Прикраси кола Мартинівки серед матеріалів салтівської культури: аналіз даних - Володарець-Урбанович, Я.В. (Археологія, 2023)
У статті розгядаються знахідки раннього середньовіччя, що характерні для скарбів кола Мартинівки і пеньківської та колочинської культур із
пам’яток і комплексів салтівської культури. Представлені трапецієподібними підвісками, ворворкою
та поясними прикрасами геральдичного кола. In the paper jewellery from sites and complexes of the Saltiv culture, which do not chronologically fit within the boundaries
of its existence, is considered. The studied jewellery is typical for the hoards of Martynivka circle (group II, subgroup 1). It is
represented by four burial complexes and one hoard.
Dmytriivka cemetery was investigated by S. Pletneva. Two trapezoidal pendants ornamented with punched rows of dots on
the edge come from catacombs no. 151 and no. 154 (fig. 1A: 1). Items from the Khatskivskyi hoard, the Kovrai locality, and
three finds from the Luchistoye burial ground are known with such an ornamentation system. In general, such pendants can be
dated by the 5th—7th centuries (fig. 1).
Sukha Homilsha cemetery 1 was investigated by V. Mikheev. Burial no. 54 contained a vorvorka (fig. 2). Burial date: late
8th—early 9th centuries. Analogies in size are presented in several hoards, in ornamentation — from the settlement of Kryvets 4.
In general, these items are typical for the hoards of Martynivka circle, the second half of the 6th— the middle third quarter of the
7th centuries.
Bochkove cemetery has been studied by O. Laptev since 2014. Grave no. 2 (fig. 3; 4) contained two trapezoidal pendants
ornamented with four spherical protrusions and two rows of pressed dots along the edge (fig. 5; 6). Similar pendants are associated
with the Penkivka monuments and hoards of the Martynivka circle.
Myrna Dolyna hoard was discovered in 2019. The complex includes: 1) blacksmith tools and several iron items (fig. 7:
1—11); 2) four blooms (fig. 7: 12—15); 3) fragments of a bronze cauldron and a pair of phaleras (fig. 8); 4) heraldic belt
decorations, including matrices and semi-finished products (fig. 9; 10); 5) Roman coins (fig. 11). Only six heraldic decorations
(fig. 9: 1-3; 10: 1—3) are known among Slavic antiquities at the level of broad analogies.
All the considered sites of the Saltiv culture with finds of jewellery from the Martynivka circle are concentrated in the
Siverskyi Donets basin. Both individual finds and treasures are known here. In the upper reaches of the river, monuments of the
Kolochyn culture are known, and below — of the Penkivka culture.
The chronology of the complexes of the Dmytriivka cemetery and the Myrna Dolyna hoard can be determined within the
general framework of the existence of the Saltiv culture. However, the chronology of burial no. 54 of the Sukha Homilsha-1,
burial no. 2 of the Bochkove cemetery and the chronology of the Martynivka circle decorations differ by almost a century
(table 1). Consequently, such adornments could be found by the inhabitants of the Khazar Khaganate and reused in everyday life or attire.